RHA_SSA: partial cement replacement in green concrete / Nuraini Tutur ... [et al.] - Tutur, Nuraini; Mat Daud, Nurhidayati; Muhamad Azlan, Hafizah; Hamzah, Nurakmal (2020)
Sludge is an unavoidable product of wastewater treatment and creates problems of disposal. For highly urbanized cities, sludge disposal by land filling might not be appropriate due to limitation of land. Using RHA_SSA for this study will encourage Malaysia to build more low carbon and sustainable building construction. Finding more alternative materials in enrich concrete structure and at the same time promoting the environmental sustainability is a must for Malaysia as developing country with increasing number of infrastructures built throughout the year. This research had been studied the effect of partial replacement of cement by Sewage Sludge Ash (SSA) and Rice Husk Ash (RHA). The effects on the nature of concrete exhibited mechanical properties of concrete such as compressive strength, water absorption, from a combination of sewage sludge ash and rice husk ash at different proportions. There were 108 samples had been prepared at different percentages of replacement of cement by using sewage sludge ash and rice husk ash. RHA_SSA are used as partial replacement of cement for 10%, 20%, 30%, 40% and 50% in the concrete. The samples had been tested with compressive test. From the results, initially, there was an increment compressive strength of concrete at 10% amount replacement SSA and RHA, but the compressive strength declined when the amount replacement SSA and RHA are developing more than 10%. In addition, the concrete also showed increasing of compressive strength within the additional curing period, which was 7 days, 14 days and 28 days. Therefore, there is potential to reuse this waste material as part of construction materials and for future researches in minimization of waste.